STUDI FENOMENOLOGI: KEPUASAN PASIEN TERHADAP PELAYANAN KEPERAWATAN DENGAN ASURANSI BPJS PBI - Emelyana Yuliana sugianto EF; Husnul Khotimah; Sri Astutik (Citra Internasional Institute, 2025)
The National Health Insurance Program (JKN) through BPJS Kesehatan aims to provide equal access to healthcare services, especially for recipients of contribution assistance (PBI). However, complaints persist regarding inpatient nursing services, including limited facilities, unresponsive staff, and lack of empathy. This raises questions about the satisfaction of BPJS PBI patients with nursing services. This study aims to determine the satisfaction of BPJS PBI patients with nursing services in the inpatient ward of Waluyo Jati Regional Public Hospital, Kraksaan-Probolinggo. Using a qualitative approach with a descriptive phenomenological method, eight participants were purposively selected based on criteria: adult patients, active BPJS PBI users, able to communicate effectively, and willing to share their experiences. Data were collected through semi-structured in-depth interviews, field observations, and documentation, with data validity ensured through source and method triangulation. Analysis followed the stages of data reduction, presentation, and thematic conclusion. Five themes emerged based on the SERVQUAL dimensions: Patients expressed satisfaction with the facilities and cleanliness of the inpatient rooms (tangible), perceived the nurses' performance as professional and consistent (reliability), and experienced prompt responses to their complaints (responsiveness). Moreover, the nurses’ friendly and polite demeanor provided a sense of security (assurance), and good communication made patients feel respected, even as recipients of subsidized services (empathy). In conclusion, Nursing services for BPJS PBI patients are viewed positively, particularly in terms of nurse attitude and responsiveness. Overall, patient care at RSUD Waluyo Jati Kraksaan received a favorable evaluation across all five SERVQUAL dimensions